TNI Died While Serving Disciplinary Punishment - Nasib Mangoloi Situmorang, Bartimeus Nicomama Hutabarat, Asan Petrus (Journal of Medical Care Research and Review, 2022)
Introduction: at the end of February 2020 the big family of the Dawolo Nias clan was shocked by the news that Tulus Sahputra Dawolo, a member of the Special Raider Infantry Battalion 136 / Tuah Sakti Kodam XVI / Pattimura Ambon, died while serving a disciplinary sentence. The victim’s body was returned to Nias and buried in the family cemetery, but the family suspected that the cause of the victim’s death was unnatural because the family saw a photo of the victim during his lifetime which showed his body was covered with bruises. Finally the family reported the matter to the Military Police of the XVI / PATTIMURA REGIONAL COMMANDO. In accordance with the KODAM XVI / Pattimura Military Police investigator’s letter number R / 68 / III / 2020 dated March 9, 2020, on March 12, 2020, the graves of the victims were carried out. Case Report: It was reported that a male victim, the initials TSD, a member of the Army, Yonif RK 136 / Tuah Sakti Ambon unit, died while serving a disciplinary sentence on Saturday, February 29, 2020 at around 14:48 WIT by a Puskesmas officer. The victim was buried on March 7, 2020 in Nias. The family suspected that the victim died as a result of mistreatment while serving a disciplinary sentence, so the case was reported to the police. So on March 12, 2020, an exumation and autopsy of the body was carried out according to a written request from the XVI / PATTIMURA MILITARY POLICE REGIONAL COMMAND, Number: R / 68 / III / 2020, 9 March 2020. Result: The victim found bruises on the stomach, abrasions on the head, forehead, eyelids, chin and blood infiltration on the inner scalp and on the right side of the stomach, bleeding under the thin membrane of the brain. There were stitches found in the crease of the right elbow. Investigations (anatomical pathology) of dams almost all organs. The Criminalistic Laboratory examination did not find any raw material for gasoline. Discussion: Based on the history of the investigator who immediately saw the victim shortly after the victim died, bruises were found all over the victim’s body, this is also in accordance with the notification of the family when asked by showing a photo of the victim with bruises on her back before she died. So from the history and forensic examination of the victim’s death as a result of the torture he experienced, which caused bleeding under the thin membrane of the brain. Conclusion: From the results of external and internal examinations as well as supporting examinations it is concluded that the cause of death of the victim was blunt trauma to the head which resulted in bleeding under the thin membrane of the brain. Keywords: Blunt Trauma, Subaracnoid Hemorrhage